Effective Method Using a Stool in Cardiopulmonary Resuscitation (CPR) on Dialysis Chair - Takeshi Ifuku; Takashi Hitosugi; Yoshfumi Kawakubo; Tomoyuki Tanaka; Kazuto Doi; Takeshi Yokoyama (Emergency Medicine International)
Background. Heart failure is the leading cause of death in dialysis patients. Cardiac arrest due to hypotension may also occur during dialysis therapy. If cardiac arrest is elicited, manual chest compressions (MCCs) should be started as soon as possible. However, all types of dialysis chairs are not stable for MCC, because there is no steady support between the backboard of the dialysis chair and the floor. These conditions may alter the effectiveness of MCC. Methods. We investigated whether a round chair is effective in supporting the dialysis chair for MCC. Four adult males performed MCC on a mannequin placed on three dialysis chairs. MCC was performed in sets of 2 (each set was 100 times per minute) per person, with and without a round chair. A total of 4,800 compressions were performed by four executors. Results. When the chair was not used as a stabilizer, the mean values of the fluctuation range were 20.8 ± 8.1 mm, 18.7 ± 5.5 mm, and 12.8 ± 1.8 mm, respectively. When the chair was used, the mean values of the fluctuation range were 6.1 ± 1.1 mm, 7.5 ± 2.1 mm, and 1.0 ± 0 mm, decreasing by 70%, 59%, and 92%. Conclusion. MCC performed with the stool under the backrest as a stabilizer was effective in supporting the dialysis chair.